Drawing conclusions: perceptions of the New Zealand agricultural landscape - Amy West (Landscape Review, 1996)
When I made the decision to finish my undergraduate education in New Zealand, I was barraged with comments about 'the beautiful natural landscapes', 'Oh you'll love the natural beauty' and 'They have such a diverse wild landscape'. However it was the aversion to comments about the agriculture which interested me. 'There are more sheep than people' is what I heard, yet where was the talk about the land which these sheep occupied? So began my quest, both as a landscape architect and as an artist, to record what there was to the New Zealand agricultural landscapes.